MODUL KIMIA BERBASIS ETNOSAINS: PEMANFAATAN TRADISI PEWARNAAN KAIN SARUNG SUKU KAJANG SEBAGAI WAHANA PENINGKATAN MOTIVASI BELAJAR PESERTA DIDIK SMK - Nirmawati; Lolo Allo, Eda; Fadly, Dewiyanti (STKIP Subang, 2026)
This study was designed to produce a chemistry module grounded in an ethnoscience approach, employing the traditional fabric dyeing practice of the Kajang community as a contextual medium for Grade X Fashion Design students at vocational high schools (SMK). The root problem driving this research is the disconnect between general subject groups, particularly science (IPAS) containing chemistry concepts, and productive subject groups within the SMK environment. This condition leads to weak learning motivation among students toward chemistry materials. The study adopts a Research and Development (R&D) paradigm following the 4D development framework consisting of Define, Design, Develop, and Disseminate stages. During development, this module integrates the STEAM (Science, Technology, Engineering, Arts, and Mathematics) framework with local Kajang cultural knowledge. Assessment by subject matter expert validators showed a very feasible category, media validators provided a feasible rating, and overall student responses demonstrated highly positive reactions. Module implementation proved capable of boosting learning motivation measured through questionnaire instruments and chemistry concept comprehension assessments. Research findings confirm that involving ethnoscience in vocational chemistry learning through local cultural contexts not only sharpens conceptual mastery but also reinforces students' cultural identity while increasing the relevance of subject matter to their workplace demands